The association between acupuncture therapy and the risk of reduced pressure ulcers in dementia patients: A retrospective matched cohort study - Chia-Yu Huang; Mei-Yao Wu; Ming-Cheng Huang; Teng-Shun Yu; Hung-Rong Yen (Integrative Medicine Research)
Background: The pressure ulcer is a complication developed from dementia. The aim of this study is to study the association between the development of pressure ulcers and the use of acupuncture therapy in patients with dementia. Methods: We performed a retrospective 1:1 propensity score-matched cohort study to investigate the association between acupuncture therapy and the risk of pressure ulcers in patients with dementia. Results: A total of 8,994 patients were identified, 237 patients in the acupuncture cohort and 362 patients in the no-acupuncture cohort developed pressure ulcers. A reduced cumulative incidence of pressure ulcers was observed in the acupuncture cohort (P<0.001). The association between acupuncture and reducing the incidence of pressure ulcers was not affected by sex, age, residence, income, or comorbidities. The variables of etiologies to cause dementia did not change the final result. In the subgroups analyses, the patients without medication for dementia control had a significantly lower rate of pressure ulcers development when they had accepted acupuncture therapy (log-rank test, P<0.001). Conclusion: Our results revealed the association between acupuncture therapy and a reduced incidence of pressure ulcer development in patients with dementia. This finding offers important ideas for further research.